The impact of risk factor trends on intracerebral hemorrhage incidence over the last two decades—The Tromsø Study ... - Carlsson, Maria; Wilsgaard, Tom; Johnsen, Stein Harald; Liv-Hege Johnsen; Maja-Lisa Løchen; Njølstad, Inger; Mathiesen, Ellisiv Bøgeberg (Figshare, 2018)
BackgroundStudies on the relationship between temporal trends in risk factors and incidence rates of intracerebral hemorrhage are scarce.AimsTo analyze temporal trends in risk factors and incidence rates of intracerebral hemorrhage using individual data from a population-based study.MethodsWe included 28,167 participants of the Tromsø Study enrolled between 1994 and 2008. First-ever intracerebral hemorrhages were registered through 31 December 2013. Hazard ratios (HRs) for intracerebral hemorrhage were analyzed by Cox proportional hazards models, risk factor levels over time by generalized estimating equations, and incidence rate ratios (IRR) by Poisson regression.ResultsWe registered 219 intracerebral hemorrhages. Age, male sex, systolic blood pressure (BP), diastolic BP, and hypertension were associated with intracerebral hemorrhage. Hypertension was more strongly associated with non-lobar intracerebral hemorrhage (HR 5.08, 95% CI 2.86–9.01) than lobar intracerebral hemorrhage (HR 1.91, 95% CI 1.12–3.25). ...